PEMBERDAYAAN PETANI GARAM DI DESA LAM UJONG MELALUI TRANSFER TEKNOLOGI PEMBUATAN GARAM SPA DAN SABUN CAIR - Irwan, Irwan; Illian, Didi Nurhadi; Putri, Cut Namira; Elisa, Sofia; Deria, Salsabila; Setiawan, Ichsan; Miswar, Edy; Putra, Dedi Fazriansyah; Nurliza, Eli; Azmi, Nurul (Jurnal Abdi Insani, 2024)
Lam Ujong Village is one of the villages in the Baitussalam sub-district of Aceh Besar Regency. The majority of people in this coastal area work as salt farmers to support their livelihoods. Despite the abundant salt production, it has not significantly increased the community's income, as salt processing is limited to selling salt directly to consumers. Processing sea salt into creative, economically valuable products has not been pursued due to a lack of innovation and skills. Sea salt is rich in minerals with great potential to be utilized as a key raw material in producing spa salts and liquid soap. This community service activity will be conducted in Lam Ujong Village in 2024, in partnership with a group of salt farmers. The project will be carried out in three stages: pre-activities (socialization and initial preparation for educational activities), main activities (training and technical guidance on producing environmentally friendly spa salt and liquid soap), and post-activities (evaluation of results).The program results demonstrated a significant improvement in the technical skills and understanding of salt farmers regarding the production process of spa salts and liquid soap. This success highlights that well-targeted technology transfer can be a key driver in the economic transformation of local communities while promoting more sustainable natural resource management. Key Word: Blue economy, Spa Salt, Liquid Soap, Salt Farmers